2001
DOI: 10.1542/peds.108.3.e40
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Generalists and Subspecialists: Determinants of Career Satisfaction

Abstract: ABSTRACT. Objectives. To evaluate the work life and job satisfaction of pediatric generalists and subspecialists in comparison to each other and to a group of general internists and internal medicine subspecialists.Methods. Data were collected by survey of a national sample of 5704 general pediatricians, subspecialty pediatricians, general internists, internal medicine subspecialists, and family physicians who were selected randomly from the American Medical Association Masterfile using stratified sampling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 21 publications
1
61
0
Order By: Relevance
“…12,40 Our study supports these and other findings, which have reported that satisfaction is lowest among early career physicians, higher in mid-career, and highest in late career. 4 In a systematic review of satisfaction trends, Scheurer et al 11 interpretation of these studies was limited due to heterogeneous samples of multiple specialties.…”
Section: Discussionsupporting
confidence: 91%
“…12,40 Our study supports these and other findings, which have reported that satisfaction is lowest among early career physicians, higher in mid-career, and highest in late career. 4 In a systematic review of satisfaction trends, Scheurer et al 11 interpretation of these studies was limited due to heterogeneous samples of multiple specialties.…”
Section: Discussionsupporting
confidence: 91%
“…This may reflect changing patterns of professional activities or the preferences of a younger generation of subspecialists. 15 Given that a substantial proportion of subspecialists decide to pursue subspecialty training before or early in residency, greater flexibility in configuring some residency experiences to meet their career goals would be feasible.…”
Section: Scope Of Practicementioning
confidence: 99%
“…16,17 Studies using this instrument have examined physician career satisfaction in general internists, 18 pediatric generalists and subspecialists, 19 and women. 20 This group of studies points out an important facet of the literature on physician satisfaction: that studies may be grouped by perspective.…”
mentioning
confidence: 99%
“…Many studies have approached satisfaction from the most obvious perspective, specialty choice. For example, as previously mentioned, Shugerman 19 Other studies have used a variety of crosssectional approaches to the study of physician career satisfaction. For example, a number of studies have examined differences in contributors to career satisfaction between male and female physicians.…”
mentioning
confidence: 99%